CREATINE KINASE EXPRESSION IS PROTECTIVE IN A MOUSE COLITIS MODEL. (26th January 2023) - Hall, Caroline; Lanis, Jordi; Dowdell, Alexander; Murphy, Emily; Colgan, Sean
Abstract: BACKGROUND: We have previously identified a loss of expression of creatine pathway proteins in mucosal tissue samples from inflammatory bowel disease patients. This is important as creatine is vital to ATP buffering in energetically active cells. The goal of this study was to determine the impact of decreased creatine kinase (CK) expression on mucosal inflammation by utilizing a whole body CK Brain and CK Mitochondrial knockout mouse (CKB/MitKO) in the dextran sulfate sodium (DSS) model of acute colitis. METHODS: CKB/MitKO and matched controls were administered 1.5% DSS in drinking water for 5 days and assessed by body weight loss, disease activity index, mucosal permeability, histology and inflammatory cytokine production by Mesoscale analysis. In subsequent experiments, interferon-γ (IFN-γ) was given by intraperitoneal injection during the DSS experiment. We also analyzed transcriptional differences between CKB/MitKO and controls using a transcription factor array and western blot. Finally, we evaluated the impact of CK on the regulation of IFN-γ and transcriptional regulation of IFN-γ production in immune cells by flow cytometry. RESULTS: Loss of CKB/Mit did not result in detectable baseline inflammation or barrier dysfunction in CKB/MitKO mice as compared to controls. However, in the setting of the chemical irritant DSS, CKB/MitKO mice had significantly increased weight loss, disease activity, intestinal permeability, histologic inflammation and decreased colon length. While control mice treated with DSS had significant increases in mucosal IFN-γ, the CKB/MitKO mice had strikingly absent mucosal protein concentrations of IFN-γ. Although IFN-γ is commonly considered a pro-inflammatory cytokine, it has also been shown to help promote inflammatory resolution. Therefore, we proceeded to add back IFN-γ in DSS experiments and we identified significant protection from weight loss and histologic damage with the addition of IFN-γ. We went on to identify transcription factor differences between CKB/MitKO and control splenocytes that revealed a >40-fold increase in the hypoxia responsive factor, HIF-1a, in CKB/MitKO splenocytes. We confirmed a causative relationship between HIF-1 expression and IFN-γ by treating mouse splenocytes with a HIF stabilizer and identified that HIF stabilization results in a reduction of IFN-γ production by CD4+ and CD8+ T cells. CONCLUSIONS: CK is an essential energetic regulator. Using CK knockout mice we have identified an important role for CK in regulating IFN-γ production, mediated at least in part by HIF stabilization. These findings support a novel role for CK in tissue protection by immune regulation during acute colitis. Better understanding the role of energetics and the creatine pathway in particular may provide novel therapeutic options in inflammatory bowel disease.